(writings on) ... like crazy. Reflections on dance making and performing with Maja and Sonja. - Aylward, Jacqueline (Taideyliopiston Teatterikorkeakoulu, 2023)
In the written part of my thesis I reflect upon my personal history and qualities as a dancer and dance maker. I unpack how this functions in my recent collaborative performance making. I situate myself within both Australian and European contexts and discuss some of the particular qualities and difficulties of this. I am critical of the universalising tendencies in Contemporary and Postmodern dancemakers and theoreticians arguing in favour of a more specific discourse. I attempt to model this in my own writing. Throughout the written thesis I use the artistic part of my thesis …like crazy (2023) as a focal point for discussing themes and topics. The images included in the thesis come from professional photography taken of artistic work, from rehearsals and of screenshots of personal messages. I use mainly artistic references to situate my work because this is the body of knowledge through which much of my understanding has been formed - in particular I look to Mette Invargten’s 50/50. I touch upon Post-Lacanian and Deluzian theories of the singularity to broaden my discussion of solo dance. I include Susan Sontag’s explanation of Camp as a possible way to categorise some of the artistic work. I turn to my fellow dance maker Maja Kalafatić to bring in a different inside perspective of the working and cite personal feedback from my peers to help see my work from the outside place. Throughout the writing there are my personal reflections upon and descriptions of dance and dance making. Overall, my approach is that of an artist writing within the context of academia and the style of writing/performative authorial voice is a product of this. I encourage my reader to also take their own approach to the text. In the first chapter, titled Looking through lineage, I have an autobiographical approach. Opening understandings of contemporary dance, postmodern dance, Camp and the impact of working with First Nations choreographers. In the second chapter, I discuss solo dance making and performing. I use my naked dance in …like crazy as a central pivot point. In this chapter I discuss the broader topics of dance making, solo dance and singularity. Here I make use of post-Lacanian and Deleuzian thinking. I also explain how I personally approach dance making through a mixture of choreography and improvisation. Finally, I place solo dance in relation to the social and more than human world. The third chapter is my favourite. I discuss and reflect upon my collaboration with Maja and Sonja. I discuss our way of working as being driven by desire and reflecting the approach outlined in Audre Lorde’s Uses of the Erotic: The Erotic as Power. I look at what did and didn't work so well in our process and consider the role of witnessing in our work. In the last chapter I take up the specific theme of naked dancing. I give some context, attend to other dancers talking about dancing naked and then outline my own experiences. I end by considering naked dancing and the audience's gaze. Here I introduce Laura Mulvey's gaze theory and open up how I act as a spectator of naked dance through a personal anecdote of watching Mette Invargsten's performance of 69 positions. To conclude I summarise my writing and look towards upcoming artistic outcomes that grow from the artistic and written thesis. I propose for myself ways in which this upcoming work can be informed by what has come before and become something other.
Keywords: ... like crazy; fi=tanssi|sv=dans|en=Dance Performance|